Novel molecular MRI approaches to the detection of brain metastasis - Zarghami, N (2019)

(untitled)
Secondary brain cancer (brain metastasis) is a leading cause of cancer morbidity and mortality. As treatments for primary tumours and systemic metastatic disease improve, the significance of brain metastasis as a cause of death increases. The poor survival of patients with brain metastasis is partly attributed to the unique microenvironment of the brain, includes the blood-brain barrier (BBB), which limits penetration of systemics cancer therapies and imaging contrast agents, and partly to the late stage of diagnosis. Current diagnosis relies on breakdown of the BBB, which only occurs at later stages of metastasis progression and, thus, delaying the introduction of potential treatments. To address this critical issue, development of novel molecular magnetic resonance imaging (MRI) contrast agents for the detection of brain metastasis at the early stages of formation was the overall focus of this thesis.